The effects of subcutaneous Tirzepatide on obesity and overweight: a systematic review and meta‐regression analysis of randomized controlled trials - Rohani, Pejman; Malekpour Alamdari, Nasser; Bagheri, Seyedeh Elaheh; Hekmatdoost, Azita; Sohouli, Mohammad Hassan (Frontiers in Endocrinology, 2023)
Background: Despite the fact that obesity and overweight are serious major health problems worldwide, fighting against them is also considered a challenging issue. Several interventional studies have evaluated the potential weight-reduction effect of Tirzepatide. In order to obtain a better viewpoint from them, this study aimed to comprehensively investigate the effects of subcutaneous Tirzepatide on obesity and overweight.Methods: Scopus, PubMed/Medline, Web of Science, Cochrane, and Embase databases were searched using standard keywords to identify all controlled trials investigating the weight loss effects of Tirzepatide.Pooled weighted mean difference and 95% confidence intervals were achieved by random-effects model analysis for the best estimation of outcomes. The statistical heterogeneity and publication bias were determined using the Cochran's Q test and I 2 statistics and using the funnel plot and Egger's test, respectively.Results: Twenty three treatments arm with 7062 participants' were included in this systematic review and meta-regression analysis. The pooled findings showed that Tirzepatide vs placebo significantly reduced body weight (weighted mean difference (WMD): -11.34 kg, 95% confidence interval (CI): -12.79 to -9.88, P< 0.001), body mass index (BMI) (WMD: -3.11 kg/m2, 95% CI: -4.36 to -1.86, P< 0.001), and waist circumference (WC) (WMD: -7.24 cm, 95% CI -10.12 to -4.36, P< 0.001). These reductions were even greater, especially with higher doses and duration of Tirzepatide.Conclusions: Tirzepatide medication had significant effects on weight management with the reduction of body weight, BMI, and WC. Administration of Tirzepatide can be considered a therapeutic strategy for overweight or obese people.